DISTRIBUSI EKONOMI ISLAM DALAM PERSPEKTIF PENDIDIKAN QS. AL-ISRA’ AYAT 29-30 - Sugianto, Efendi (Tawshiyah: Jurnal Sosial Keagaman dan Pendidikan Islam, 2023)
Wealth can be produced in a country with large amounts, but if its distribution is not based on true and fair principles, then the country will not achieve prosperity. Islam takes the middle path that can help enforce a fair and just system. Islam also does not give everything, nor unlimited rights in owning personal weaith for a person in the field of production, nor does it attract a person to an economic process system that under this system he cannot obtain, and has wealth independently. how is the definition of distribution in Islamic economics in the educational perspective Qs. Ai-lsra verses 29-30, and How is the Mechanism in the distribution of Islamic economy in the educational perspective Qs. Al-lsra verses 29-30. The study uses a descriptive analysis method, which is library research that provides a clear, objective, systematic, analysis of Islamic economic distribution in the educational perspective Qs. Ai-Isra verses 29-30. It can be drawn the common thread that distributing the economy or finances, a person is prohibited from applying miserly and in effect extravagant. but the best thing in distributing the economy and finance is to maintain the principle of balance and sufficiency. God who certainly expands or narrows the sustenance of a person, family, community, or nation and country; For Allah is Supra-Knowing, Supra--Seeing